Planning of Information Systems Needs for Parking Space in Private Colleges of Banjarmasin City: Perencanaan Kebutuhan Sistem Informasi Ruang Parkir di Perguruan Tinggi Swasta Kota Banjarmasin - Nurhaeni; M.Riko Anshori Prasetya; Sitanggang, Anugrah Bakti (LPPM Universitas Sari Mulia, 2024)
Parking is one of the components or integral aspects of transportation system needs, as any journey with a private vehicle usually starts and ends at the parking lot. The study was developed using a system planning method with a functional approach described using UML Tools (Unified Modelling Language). The aim of the study is to make a plan for parking in the private college environment of Banjarmasin city using UML Tools. The study is basically a quantitative observational research that is a measured research design. System design is done using UML Tools as a modeling tool to describe how the system will work and make it easier for the system to be designed to be understood. This research is expected to be beneficial to the parking lot providers in order to create efficiency for the riders in searching for parker land not to waste time, improve security, facilitate access and minimize the occurrence of parking lot clashes with other riders seeing the number of vehicles increasing as the student mobility increases.